DOP017 Increased intestinal aryl hydrocarbon receptor expression and pathway sensitivity in Crohn's disease. (16th January 2018) - Harrow, P; McCarthy, N; Stagg, A; Lindsay, J
Abstract: Background: The aryl hydrocarbon receptor (AHR) is a transcription factor activated by dietary and bacteria-derived ligands. In mice, AHR signalling regulates specialised intestinal immune cell survival and function and activating AHR improves outcomes in diverse models of colitis. AHR gene variants are associated with susceptibility to IBD but little is known about the role of AHR in the human intestine. AHR directly regulates expression of cytochrome p450 enzymes (CYP1A1 and CYP1B1). In this study, we identify colonic cell populations responsive to AHR ligands and use quantitative assessment of CYP enzyme expression to compare resting AHR pathway activity and AHR ligand responsiveness in health (HC) and Crohn's disease (CD). Methods: Cells expressing AHR protein were visualised using both multicolour confocal microscopy of tissue sections and cytospin preparations of isolated cells. Expression of AHR and regulated genes was determined by qRT-PCR of cells isolated from endoscopic biopsies and purified by MACS or FACS sorting. Functional AHR signalling was determined by expression CYP1A1 in sorted cell populations cultured with AHR ligand (FICZ 10–100 nM) and/or antagonist (CH-223191 100 μM). Results: Expression of CYP1A1 was detected in snap-frozen whole biopsy tissue suggesting activation of the AHR pathway in vivo. AHR expression and a functional AHR pathway was detected in leukocytes (CD45+), epithelial cells (EpCAM+), stroma cells (EpCAM−, CD31−) and primary cultured fibroblasts but not endothelial cells in both HC and CD. AHR expression was significantly higher in CD45+ and CD45− cells from patients with CD compared with HC. AHR-dependent CYP1A1 expression was detectable in freshly isolated CD45+ and CD45− cells in the absence of stimulation but could be further upregulated upon exposure to ligand in vitro. There was a direct correlation between AHR expression and resting CYP1A1 expression. CD45− cell CYP1A1 expression in response to FICZ was significantly higher in CD compared with HC (Figure 1). Conclusions: This is the first demonstration of a functional AHR pathway in both immune and non-immune cell populations in the human intestine in health and IBD. Our results suggest basal AHR pathway activity in vivo. Crohn's disease associated changes in AHR expression and function may represent changes in cell populations, intestinal ligand exposure or sensitivity in the pathway. A better understanding of the role of AHR in diverse intestinal cells, will inform the use of ligands as potential therapeutic agents in IBD.